Penerapan Metode Thresholding Pada Proses Transformasi Citra Digital - Fakhrurrozy Cahyadi, Muhammad; Syahputra, Siswan; Alfhi Syari, Mili (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Book is a window to the world. By reading books, we can get a variety of knowledge that we do not know. The meaning of books as windows to the world can be doubted today. Given the internet provides a lot of information with a much more attractive appearance. Both books and the internet provide a wealth of information and knowledge. But in fact books are still the mainstay of accurate sources of knowledge. A lot of information on the internet is in fact not supported with accuracy. Even in the world of higher education, books are the main reference source in scientific writing. However, old books that may have started to become dull and the writing can no longer be read resulted in the reader of the book not being able to know the knowledge contained in the old book. Based on observations, it is necessary to build a computerized system so that the writings in the book can be read again. One method that can be used is the Thresholding method. The system is designed with MATLAB programming application. In this process, it is necessary to scan or take photos/pictures from cellphone cameras from old book manuscripts to be processed on the system using the Thresholding method. After carrying out the testing process on several images of old books, better results were obtained so that the writing on the manuscript could be seen more clearly with different threshold values for each image entered into the system.